Antibacterial Test of Kedondong Hutan Leaf (Spondias pinnata) Against Salmonella typhi - Rangga, Febby Alvanda; Amarantini, Charis; Budiarso, Tri Yahya (Jurnal ILMU DASAR, 2024)
Kedondong hutan (Spondias pinnata) is a plant belonging to the Anacardiaceae family, plant that grows a lot in the Sulawesi area, one of which is in the Poso area, Central Sulawesi. The surrounding community uses this plant as a traditional food preparation which is often called the "Arogo Onco" by the community. Kedondong hutan contains active compounds that have the potential as antibacterial, namely flavonoids, saponins and tannins. The purpose of this study was to determine the potential of forest kedondong leaves in inhibiting the growth of Salmonella typhi bacteria. The extraction process was done the decoctation method using aquadest and while the antibacterial test was done using the diffusion method against three bacterial strains namely Salmonella typhi BPE 127.1 MC, BPE 122.4 CCA and NCTC 786. The results showed that the leaf extract of kedondong hutan (Spondias pinnata) contained flavonoids, saponins and tannins with the results of the analysis of total flavonoids 1514,9 mgQE/g, saponins 0.613% and tannins 8,94 mgTA/g. The results of the antibacterial test showed the greatest inhibitory power at a concentration of 100%. Salmonella typhi BPE 127.1 MC, BPE 122.4 CCA, NCTC 786, was the inhibition zone 17.67±0.58 mm, 15.67±0.58 mm and 20.33±0.58 mm were included in the category of strong inhibition zone.